Sledging related spinal injuries and fracture patterns: a report on five cases. Issue 5 (1st October 1999) - Basu, S; Makwana, N K; Khazim, R
Abstract : The cases are reported of five patients who presented to The Queens Medical Centre, Nottingham after a sledging accident. All five patients presented consecutively during the first weekend in 1997 having sustained the accident in the same public park. The mechanism and subsequent fracture type is described for each. These injuries are preventable, and increasing public awareness of the risk of sledging in public places may reduce the incidence.